1994
DOI: 10.1002/bjs.1800810148
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open appendicectomy: A prospective assessment

Abstract: A prospective study of 200 consecutive patients with suspected acute appendicitis was performed to compare open and laparoscopic appendicectomy. Formal randomization was precluded by instrument availability. Some 100 patients underwent laparoscopic appendicectomy (conversion to laparotomy was carried out in five) and 100 had conventional surgery. The groups were similar in sex ratio, age, degree of appendiceal inflammation and antibiotic treatment. The mean duration of open appendicectomy was 46 min and of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(40 citation statements)
references
References 10 publications
6
34
0
Order By: Relevance
“…A study from Nepal 12 also showed significant decrease in the length of hospital stay in patients undergoing LA (p<0.001), which is consistent with the findings of other studies. [13][14] In accordance with other studies, 2,12 there was fewer wound infection in LA group 2.5%, with the post operative complication of 8.5%. In a study by Tate et al they highlighted the difference in wound complication rates as a major benefit of laparoscopic appendicectomy.…”
Section: Discussionsupporting
confidence: 87%
“…A study from Nepal 12 also showed significant decrease in the length of hospital stay in patients undergoing LA (p<0.001), which is consistent with the findings of other studies. [13][14] In accordance with other studies, 2,12 there was fewer wound infection in LA group 2.5%, with the post operative complication of 8.5%. In a study by Tate et al they highlighted the difference in wound complication rates as a major benefit of laparoscopic appendicectomy.…”
Section: Discussionsupporting
confidence: 87%
“…Most of the published studies revealed a lower wound infection rate after LA which is in fact the sole advantage [3, 4, 7]. In our study, we found a wound infection rate of 3.5%, which is rather low and within the range of the data from other studies [7, 8, 9, 10, 11, 12, 13, 14, 15, 16]. …”
Section: Discussionsupporting
confidence: 39%
“…Generally, the available data show no clear evidence of patient benefit after LA [8, 9, 10, 11, 12, 13, 14, 15, 16]. Most of the published studies revealed a lower wound infection rate after LA which is in fact the sole advantage [3, 4, 7].…”
Section: Discussionmentioning
confidence: 99%
“…24 According to Jalujan Mompean 25 early bowel obstruction was seen in 4 after laparoscopic appendicectomy and 5 cases after open appendicectomy incidence of bowel obstruction did not differ between laparoscopic appendicectomy and open appendicectomy in either group.…”
Section: Discussionmentioning
confidence: 95%